Natural ceramic nanoparticles ‒ layered aluminosilicates as an active phase of polymer nanocomposites and their potential application in medicine - Stodolak-Zych, E.; Dzierzkowska, E.; Rapacz-Kmita, A. (Wydawnictwo Politechniki Łodzkiej, 2018)
"Developing knowledge in the field of nanotechnology and its potential medical applications in many cases may provide solutions that both patients and doctors expect. However, one should be aware that the application of nanotechnology entails the need to answer a number of bothering questions about the safety of using nanoparticles as well as nanomaterials based on them. The excess surface energy of materials at the nanometer scale, resulting from the strongly developed surface, can be used as a carrier of drugs, proteins, e.g. enzymes or antigens. Particularly interesting here are the naturally occurring layered aluminosilicates (e.g. smectites), whose variety of forms, availability, ease of extraction, as well as the repetition of purification and the possibility of chemical modification, allow the use as stand-alone nanoparticles, but also as fillers in the polymeric phase. The paper presents the possibilities of using aluminosilicate particles based on montmorillonite (MMT) and kaolinite (K) in biomedical applications."

"Rozwijająca się wiedza w zakresie nanotechnologii i jej potencjalnego zastosowania medycznego w wielu przypadkach dostarczać może rozwiązania, na które oczekują zarówno pacjenci, jak i lekarze. Należy mieć jednak świadomość, że zastosowanie nanotechnologii pociąga za sobą konieczność odpowiedzi na szereg nurtujących pytań o bezpieczeństwo stosowania nanocząstek, jak i otrzymywanych na ich bazie nanomateriałów. Nadmiarowa energia powierzchniowa materiałów w skali nanometrycznej, wynikająca z silnie rozwiniętej powierzchni, może zostać wykorzystana jako nośnik leków, białek np. enzymów czy antygenów. Szczególnie interesujące są tu naturalnie występujące glinokrzemiany warstwowe (np. smektyty), których różnorodność form, dostępność, łatwość pozyskiwania, a także powtarzalność oczyszczania oraz możliwość modyfikacji chemicznej, umożliwia zastosowanie jako nanocząstek samodzielnych, ale także jako napełniaczy fazy polimerowej. W pracy przedstawionomożliwości wykorzystania cząstek glinokrzemianowych na bazie montmorillonitu (MMT) i kaolinitu (K) w zastosowaniach biomedycznych."
Keywords: nanoparticles; clay; smectite; nanocomposite; drug delivery system; nanocząstki; glina; smektyt; nanokompozyty; system dostarczania leków